2006
DOI: 10.1080/02713680500514644
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Effect on Gene Expression in the Mouse Meibomian Gland

Abstract: These findings support our hypothesis that sex-related differences exist in gene expression of the meibomian gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Our findings are consistent with the gender associated and gland specific variations in mRNA levels previously reported in rodent model salivary gland systems (20,27,28) and in lacrimal (29) and meibomian glands (30). The differentially expressed genes in these studies are involved in a wide range of biological processes, molecular functions and cellular components, including growth and development, transcription, metabolism, signal transduction, ion transport, receptor activity and protein and nucleic acid binding.…”
Section: Discussionsupporting
confidence: 79%
“…Our findings are consistent with the gender associated and gland specific variations in mRNA levels previously reported in rodent model salivary gland systems (20,27,28) and in lacrimal (29) and meibomian glands (30). The differentially expressed genes in these studies are involved in a wide range of biological processes, molecular functions and cellular components, including growth and development, transcription, metabolism, signal transduction, ion transport, receptor activity and protein and nucleic acid binding.…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies have demonstrated that factors such as strain [34,35], gender [36,37], as well as diet [38,39] and circadian variation, [40] can influence gene expressions in various organisms and tissues. In our study we created two retina samples by randomized pooling of samples from a large number of individuals aiming to cancel out the effects of such factors.…”
Section: Discussionmentioning
confidence: 99%
“…[125][126][127] Androgens appear to control 30% of the sexassociated variations in sex-related differences of the MG (in mouse). 128 Androgens have a major influence on MG structure, 129,130 aging and androgen status disorders leading to obstructive MGD with a lack of lipids at the lid margin and in the tear film, an altered lipid profile, and DE symptoms. 15,79,[131][132][133] Estrogens (in particular 17-b-estradiol) appear to negatively influence lipid secretion in MG, by suppressing genes involved in lipid biosynthesis, whereas they upregulate the expression of genes involved in lipid and fatty acid catabolism.…”
Section: Gender Sex Steroids and Evaporative Dementioning
confidence: 99%